Biochemical and biophysical studies of Trypanosoma cruzi phosphofructokinase as a target against Chagas disease. (25th February 2016) - Fernandes, Peter M; Kinkead, James; McNae, Iain; Michels, Paul; Walkinshaw, Malcolm
Abstract: Background: Trypanosoma cruzi is a protozoan parasite that causes Chagas disease, a chronic infection affecting the sympathetic nervous system; no effective non-toxic treatments are available. Inhibitors of trypanosomatid glycolytic enzymes are promising therapeutic targets, as shown by research on T brucei phosphofructokinase (PFK). The aim of this study was to investigate the structure, function, and regulation of T cruzi PFK, to provide insights into the suitability of this enzyme as a drug target. Methods: BL21(DE3) Escherichia coli cells were transformed with pET28a plasmid containing cDNA for T cruzi PFK with N-terminal hexahistidine tag, and induced with isopropyl-β-D-thiogalactopyranoside. Pellets were lysed by liquid homogenisation and purified through immobilised metal ion affinity chromatography and size exclusion chromatography. Kinetic values and inhibition were determined with an auxiliary enzyme-linked assay with pyruvate kinase and lactate dehydrogenase. Crystallisation was done via the hanging drop method in 24-well plates at 18°C. Findings: T cruzi PFK was fully purified and verified with mass spectrometry (Mascot score of 241). Dynamic light scattering indicated a homogenous sample of molecular weight 239 kDa. Apo-enzyme and holo-enzyme crystals were produced (cofactors ATP or AMP). Maximum specific activity (Vmax ) was 58·9 μmol/min per mg. ATP binding was hyperbolic (Michaelis-Menten kinetics) with Km ATP 52·9 μM. F6P binding was sigmoidal (allosteric sigmoidal kinetics) with Khalf F6P 429 μM. GTP was an alternative substrate but showed reduced activity and affinity compared with ATP. AMP was an allosteric activator, reducing Km ATP to 15 μM. F16BP was inhibitory above 2·5 mM, but no other metabolites altered activity. Novel small molecule inhibitors demonstrated sub-50 nanomolar IC50 values for T cruzi PFK, and were inactive against human PFK. Interpretation: The biophysical results indicate that T cruzi PFK is tetrameric, similar to other PFKs. Compared with T brucei PFK, T cruzi PFK has a higher affinity for ATP and F6P and similar Vmax . The relative lack of allosteric regulators can be explained by the localisation of T cruzi PFK within glycosomes. The physiological significance of GTP use is doubtful given the lack of a glycosomal mechanism for regenerating GTP from GDP. Novel inhibitors bound allosterically, showing that they have great promise as candidate drugs. Funding: Wellcome Trust.